Manajemen pemeliharaan Domba Garut tipe tangkas dan pedaging - Putrayana, Adhira Alfansa; Aulia Miftahunnisa Exa Putriyana2; Nurmeidiansyah, An An (Fakultas Pertanian Universitas Majalengka, 2024)
Garut sheep, one of Indonesia's leading livestock commodities, has two main types that are distinguished based on their rearing purpose, namely the bantam and meat types. Based on several aspects, the maintenance management between the two types of Garut sheep has quite exciting differences to be highlighted. This study aimed to evaluate the difference between the management of bantam Garut sheep and meat Garut sheep. This research used an internet-based literature study approach based on the Google Scholar, Scopus, and Mendeley application databases. The article search strategy used the keywords